2018
DOI: 10.1111/acps.12896
|View full text |Cite
|
Sign up to set email alerts
|

Mixed states in bipolar and major depressive disorders: systematic review and quality appraisal of guidelines

Abstract: The unmet needs for the mixed symptoms treatment were associated with diagnostic issues and limitations of previous research, particularly for maintenance treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 199 publications
(230 reference statements)
1
51
0
2
Order By: Relevance
“…Our data suggest that individuals with bipolar disorder who experience AD are also more likely to have mixed manic episodes in their lifetime, which is in line with previous research that has identified a subtype of bipolar patients characterized by a clinical course of mixed episodes. 24,28,32 Our finding that agitated activity in bipolar depression is associated with concurrent depressive symptoms that have been shown to be common in mixed manic episodes 23,36 (poor concentration, poor appetite, insomnia, and suicide behavior) in other samples is of relevance here, and should be examined within the same sample. We do not have detailed symptom data for individual mixed manic episodes to be able to examine this in our sample.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our data suggest that individuals with bipolar disorder who experience AD are also more likely to have mixed manic episodes in their lifetime, which is in line with previous research that has identified a subtype of bipolar patients characterized by a clinical course of mixed episodes. 24,28,32 Our finding that agitated activity in bipolar depression is associated with concurrent depressive symptoms that have been shown to be common in mixed manic episodes 23,36 (poor concentration, poor appetite, insomnia, and suicide behavior) in other samples is of relevance here, and should be examined within the same sample. We do not have detailed symptom data for individual mixed manic episodes to be able to examine this in our sample.…”
Section: Discussionmentioning
confidence: 90%
“…23,28,36 Previous literature is not consistent regarding the association that we found between concurrent agitated and slowed activity. 24,28,32 Our finding that agitated activity in bipolar depression is associated with concurrent depressive symptoms that have been shown to be common in mixed manic episodes 23 Moreover, individuals who experience both AD and dysphoric mania during their lifetime could belong to a subtype of bipolar disorder characterized by mixed episodes with a high risk of suicide attempt for which antidepressant medication is not recommended. Similar to our results they found that AD was most strongly associated with somatic symptoms and anxiety, while dysphoric mania was associated with manic thought and hostility.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Evidence regarding pharmacotherapy for mixed depression is even more scarce. Nonetheless, six international guidelines have mentioned pharmacological strategies for mixed depression [26]. The mainstay (2) · LUR + Li/VPA (1) · OFC (2) -· ASN (4) CINP-BD 2017 -· OLZ + MS (2) · SGA: ARP, ASN, OLZ (3) , ZPD (4) · MS: CBZ (3) , VPA (4) · OFC (4) -RANZCP Mood Disorders CPG · SGA: OLZ, QTP · MS: VPA · SGA (OLZ, QTP) or VPA + AD · OLZ + VPA --…”
Section: Pharmacotherapy For Mixed Depressionmentioning
confidence: 99%
“…· SGA: LUR, ASN, QTP, QTP-XR, ARP, ZPD (1) , OLZ, CAR (2) · MS: LMT, VPA, Li (2) · SGA + MS (Li/LMT/VPA) · Li + VPA · Li/VPA + LMT · OFC · MS: CBZ (3) · CBZ + Li (3) · Li + pramipexole (3) · Li + ECT (3) · MS or SGA + SSRI/ bupropion/ MAOI (3) WFSBP mixed states -· Z PD + TAU · SGA: LUR, OLZ (3) · MS: CBZ (3) · ECT This table is adapted from a 2018 report by Verdolini et al [26] (Acta Psychiatr Scand). (1) -(4), grades of evidence; AD, antidepressants; ARP, aripiprazole; ASP, asenapine; CAR, cariprazine; ECT, electroconvulsive therapy; Li, lithium; LMT, lamotrigine; LUR, lurasidone; MAOI, monoamine oxidase inhibitor; MS, mood stabilizers; OFC, olanzapine + fluoxetine; OLZ, olanzapine; QTP, quetiapine; SGA, second-generation antipsychotics; SSRI, selective serotonin reuptake inhibitor; TAU, treatment as usual; VPA, valproic acid; ZPD, ziprasidone.…”
Section: Mixed Depression Guidelinesmentioning
confidence: 99%